SOSIALISASI PENGGUNAAN APLIKASI KAHOOT UNTUK MENINGKATKATKAN PROSES PEMBELAJARAN INTERAKTIF DI SMA NEGERI 1 KAMBERA - Susanti Djaty Oy; Dominikus Tay Ngunju Amah; Shintya Damayanti Rambu Hada; Claryn Atwyanti Viona David; Ana Rambu Wahi Tamu; Ferdinand Ndawa Lu Remindima (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Science and technology have developed very rapidly over time; therefore, their advancement has had a significant impact on various aspects of human life. One form of innovation that can be utilized in the educational field is the use of the Kahoot application as an interactive quiz-based learning medium. In this context, PLP II students who carried out their PLP II program at SMA Negeri 1 Kambera conducted a socialization activity on the use of the Kahoot application as an effort to support teachers and students in implementing technology-based learning. This socialization activity was conducted at SMA Negeri 1 Kambera with the aim of introducing the Kahoot application to teachers and students in order to enhance learning motivation and interest. The methods employed included lectures, demonstrations, and hands-on practice using the Kahoot application through interactive quiz sessions. The socialization of the Kahoot application at SMA Negeri 1 Kambera successfully enhanced the learning process carried out by both students and teachers through interactive quizzes. This was evidenced by a significant improvement in understanding, as pre-test scores (10–50, low to moderate) increased substantially in the post-test to 60–100. Furthermore, the success of the activity was also reflected in the program satisfaction score, which reached 89% and was categorized as Very High.